Psychometric Properties of Scales Measuring Resilience in U.S. Latinx Populations: A Systematic Review (Mary Ann Liebert, 2023)
Objectives: Instruments used to measure resilience have typically been developed in European or Anglosphere countries and emphasize personal factors of resilience. In addition to being a quickly growing ethnic minority group in the United States, Latinx individuals face unique stressors and protective factors that may contribute to resilience. This review sought to determine the extent to which instruments measuring resilience have been validated in U.S. Latinx populations and what domains of resilience those scales capture. Methods: A systematic literature review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards and included studies describing psychometric properties of resilience scales for Latinx individuals living in the United States. Articles were assessed for quality of psychometric validation; scales used in the final studies were assessed for representation of domains of the social ecological resilience model. Results: Nine studies were included in the final review examining eight separate resilience measures. The populations of these studies were heterogeneous geographically and demographically; more than half the studies only included Latinx populations as a subgroup. The breadth and quality of psychometric validation were variable across studies. The domains represented by the scales in the review most heavily assessed individual domains of resilience. Conclusion: The literature to date on psychometric validation of resilience measures in Latinx populations in the United States is limited and does not robustly capture aspects of resilience that may be particularly meaningful for Latinx populations, such as community or cultural factors. Instruments that are developed with and for Latinx populations are necessary to better understand and measure resilience in this population.